Pengaruh Penambahan Hebel (Bata Ringan) dan Batu Apung pada Tanah Terhadap Nilai Kompaksi - Lola; Irwan; Apriyani, Ika (Paulus Civil Engineering Journal, 2025)
Depending on its kind, content, and treatment, soil can have a variety of qualities. Stabilization is therefore required to increase the soil's bearing capacity. The use of supplemental materials like pumice and Hebel (lightweight brick) is one approach to boost the soil's bearing capacity. Hebel is a lightweight, permeable material that helps ease the burden on the soil. The study was conducted in two stages: 1) Evaluating the physical properties of the soil; 2) Compaction test As per the AASHTO classification, the soil falls within the clay soil category (A-7-6). The soil falls within the category of inorganic clay soil with a low to medium degree of flexibility according to the USCS classification. Because lightweight bricks and pumice have a high lime content, which increases the soil's bearing capacity, test results showing their addition to the soil using the standard proctor showed an increase of up to 15% from the original soil.